RECOVERY OF A LOWLAND DIPTEROCARP FOREST TWENTY TWO YEARS AFTER SELECTIVE LOGGING AT SEKUNDUR, GUNUNG LEUSER NATIONAL PARK, NORTH SUMATRA, INDONESIA - Dolly - Priatna; Kuswata - Kartawinata; Rochadi - Abdulhadi (REINWARDTIA, 2006)
PRIATNA, D.; KARTAWINATA, K.; ABDULHADI, R. 2004. Recovery of a lowland dipterocarp forest twenty two years after selective logging at Sekundur, Gunung Leuser National Park, North Sumatra, Indonesia. Reinwardtia 12 (3): 237–255. — A permanent 2-ha plot of lowland forest selectively logged in 1978 at Sekundur, Gunung Leuser National Park,which is also a Biosphere Reserve and a World Heritage Site, North Sumatra,was established and investigated in 1982. It was re-examined in 2000, where remeasurement and reidentification of all trees with DBH =10 cm were made.The areas of gap, building and mature phases of the canopy were also measured and mapped. Within this plot, 133 species, 87 genera and 39 families were recorded, with the total number of trees of 1145 or density of 572.5/ha. Euphorbiaceae was the richest family with 18 species (13.5 % of the total) and total number of trees of 248 (21.7 % of the total or density of 124 trees/ha.The most important families were Dipterocarpaceae with IV (Importance Value) = 52.0, followed by Euphorbiaceae with IV = 51.8. The most prevalent species was Shorea kunstleri (Dipterocarpaceae) with IV =24.4, followed by Macaranga diepenhorstii (Euphorbiaceae) with IV = 12.4. They were the species with highest density, 34 trees/ha and 23.5 trees/ha, respectively. During the period of 18 years there has been no shift in the richest families, most importantfamilies and most important species. Euphorbiaceae was the richest family and Dipterocarpaceae was the most important family, with Shorea kunstleri as the most important species with highest importance value throughout the period. The number of species increased from 127 to 133 with increase in density by 36.8% , from 418.5 trees/ha to 572.5 trees/ha. The mortality was 25.57 % or 1.4 % per year. The diameter class distribution indicated that the forest recovery has not been complete. Trees were small, comprising 67.6 % with diameters of 10-20 cm and only two trees had diameters of 100 cm, i.e.Melanochyla caesia and Lithocarpus urceolaris. Based on the basal area of all species, the logged-over forest at Sekundur is estimated to reach the situation similar to undisturbed primary forest in 56 years after logging, but on the basis of basal area of Dipterocarpaceae such condition could be achieved in 172 years.The canopy has not fully recovered and the complete closure of gaps is estimated to take 53 years since the logging started. The canopy consisted of gap phase (24.6 %), building phase (19.7 %) and mature phase (55.7 %). During the period of 18 years the tree mortality was 25.57 % or the rate of 1.4 %/year.Euphorbiaceae experienced the highest mortality, particularly among the trees with diameters of 10-20 cm.Mortality decreased with the increase of diameters.During the same period 520 new trees of 16 species were recruited.The densities of 53 % of the species experienced changes of only one tree or no changes at all.Drastic increase in tree population occurred in light demanding species,such as Baccaurea kunstleri, Endospermum diadenum,Mallotus penangensis,Sapium baccatum and Macaranga diepenhorstii .